Sealing ability of retrograde obturation materials containing calcium hydroxide or MTA - Tanomaru-Filho, Mário; Faleiros, Frederico B C; Silva, Guilherme F; Bosso, Roberta; Guerreiro-Tanomaru, Juliane M (My University, 2011)
Newly available materials for retrograde obturation should have their sealing properties evaluated. The goal of this study was to evaluate the sealing ability of Endo CPM sealer, an MTA-based endodontic cement. Single-rooted extracted human teeth were endodontically treated. After apical sectioning, retrograde cavities were prepared. Teeth were divided into five experimental groups (n=12), in which the following materials were used: Sealer 26 (S26), white Mineral Trioxide Aggregate (MTA), Endo CPM Sealer (CPM1), Endo CPM Sealer in thicker consistency (CPM 2), and zinc oxide and eugenol cement (ZOE), and two control groups (n=3). After retrograde obturation, the teeth were immersed in 0.2% rhodamine B dye for 48 hours in a vacuum chamber Marginal leakage data were subjected to ANOVA and Tukey tests at 5% significance level. S26 presented greater sealing ability (p<0.05) than ZOE, MTA, CPM1, and CPM2, all of which had similar results (p>0.05). We concluded that Sealer 26 has the greatest sealing ability. Endo CPM Sealer, with sealing ability similar to MTA, could be used as a retrograde obturation material.
Keywords: aluminum derivative; bone cement; calcium derivative; calcium hydroxide; mineral trioxide aggregate; oxide; root canal filling material; silicate; drug combination; endodontics; human; in vitro study; materials testing; Aluminum Compounds; Bone Cements; Calcium Compounds; Calcium Hydroxide; Drug Combinations; Humans; Materials Testing; Oxides; Retrograde Obturation; Root Canal Filling Materials; Silicates